Sarcopenia as prognostic factor for survival after orthotopic liver transplantation. Issue 5 (May 2020) - Pinto Dos Santos, Daniel; Kloeckner, Roman; Koch, Sandra; Hoppe-Lotichius, Maria; Zöller, Daniela; Toenges, Gerrit; Kremer, Wolfgang Maximilian; Zimmermann, Tim; Mittler, Jens; Lang, Hauke; Düber, Christoph; Galle, Peter Robert; et al.
Abstract : Background and aim: Body composition has emerged as a prognostic factor for end-stage liver disease. We therefore investigated muscle mass, body fat and other clinical–pathological variables as predictors of posttransplant survival. Methods: A total of 368 patients, who underwent orthotopic liver transplantation (OLT) at our institution, were assessed prior to OLT and followed for a median of 9.0 years (range 2.0–10.0 years) after OLT. Psoas, erector spinae and the combined paraspinal muscle area, as well as the corresponding indices normalized by body-height squared, were quantified by a lumbar (L3) cross-sectional computed tomography. In addition, absolute body fat and bone density were estimated by the same computed tomography approach. Results: Paraspinal muscle index (PSMI) (hazard ratio 0.955, P  = 0.039) and hepatitis C (hazard rati 1.498, P  = 0.038) were independently associated with post-OLT mortality. In contrast, body fat and bone density did not significantly affect post-OLT outcome ( P  > 0.05). The PSMI also predicted one-year posttransplant mortality with a receiver operating characteristics-area under the curve of 0.671 [95% confidence interval (CI) 0.589–0.753, P  < 0.001) in male patients and outperformed individual psoas and erector spinae muscle group assessments in this regard. In male patients, a defined PSMI cutoff (<18.41 cm 2 /m 2 ) was identified as suitable determinant for sarcopenia and posttransplant one-year mortality. In female OLT-recipients, however, sarcopenia was not predictive for patient survival und a women-specific cutoff could not be derived from this study. Conclusions: Taken together this analysis provides evidence, which PSMI is a relevant marker for muscle mass and that sarcopenia is an independent predictor of early post-OLT survival in male patients. Abstract : Supplemental Digital Content is available in the text.